The public administrator in the eyes of private business perspectives on perceptions, expectations and public leadership - Kalaw, Teodoro IV (2008)
The article explores the tri-faceted nexus arising from (1) the generally dismal view of public institutions expressed by the private sector in various successive surveys over the years; (2) conventional private and public sector perceptions on the supposedly proper role of public leaders in the context of the society today; and (3) potential perspectives for identifying and addressing assumptions and expectations created by such views. In doing so, it is hoped that this article will contribute to the development of a more realistic and relevant model of the Philippine public leadership that is more attuned to the demands and needs of the Philippine economy in general, and of Filipino businesses in particular. The article starts with an analysis of the perception by the business sector regarding public institutions. It shall also analyze the model that a public servant is expected to be, a heroic leader. The article ruminates on shattering this myth and explores an alternative paradigm that relates to the handling of ethical situations in terms of "quiet leadership," and the feasibility of adopting this model of leadership for public administrators in the local settings. It then provides specific illustrations of what the mindset of a Filipino public administrator practicing quiet leadership would be like. The article concludes by linking this model of "quiet leadership" with efforts to bring about a truly Filipino discipline of public administration, mindful of the need for a change in perspective on how those in both the public and the private sectors view public leadership.
Keywords: Ethics; Public administration -- Economic aspects; Public officers; Social Weather Stations (SWS)